2001
DOI: 10.2308/bria.2001.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Management Fraud Risk Factors

Abstract: In an exploratory study, we report how 140 auditors rate the relative importance of 25 risk factors (red flags) identified in SAS No. 82. The Analytic Hierarchy Process (AHP) is used to produce a decision model for each subject, and mean decision models are reported for groups of subjects. The results indicate that management characteristics and influence over the control environment red flags were approximately twice as important as operating and financial stability characteristics red flags and about four ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 6 publications
3
52
1
6
Order By: Relevance
“…Other studies based on USA data include that of Apostolou et al (2001), who surveyed the views of auditors on the relative importance of a number of fraud risk factors. They found that fraud risk factors involving management characteristics and influence over the control environment were significantly more important than factors related to financial stability and industry conditions.…”
Section: Most Important Fraud Risk Factorsmentioning
confidence: 99%
“…Other studies based on USA data include that of Apostolou et al (2001), who surveyed the views of auditors on the relative importance of a number of fraud risk factors. They found that fraud risk factors involving management characteristics and influence over the control environment were significantly more important than factors related to financial stability and industry conditions.…”
Section: Most Important Fraud Risk Factorsmentioning
confidence: 99%
“…Asare and Wright, 2004;Bell and Carcello, 2000;Eining et al, 1997;Loebbecke et al, 1989;Pincus, 1989), Shelton et al (2001) report finding three Big Five firms that utilize a red flag checklist to identify the presence or absence of fraud risk factors. 18 Adapted from one or more of the following: AICPA (1997); AICPA (2002); Apostolou et al (2001); Bell and Carcello (2000); Eining et al (1997); Hackenbrack (1993); Davidson (1994); Zimbelman (1997). 19 The significant Pearson's product-moment correlations between ''Comp'' and both ''Trust'' (0.244) and ''Risk'' ()0.220) should be noted at this point because they were not expected.…”
mentioning
confidence: 99%
“…A deeper understanding of the de facto tone at the top could work as a preventive fraud risk factor. Although some progress has been made in this direction (see, for example, Apostolou et al 2001), the challenge rests in incorporating more fully the human side in the assessment of tone.…”
Section: Characteristics Of Obstaclesmentioning
confidence: 99%
“…2 This notion is supported by the studies suggesting tone at the top as a key fraud risk factor (see, e.g.,Apostolou et al 2001).…”
mentioning
confidence: 95%